Numerical study of earth pressures on rigid pipes with tire-derived aggregate inclusions - Ni, Pengpeng (2019)
Rigid pipes under high embankments are often installed using the induced trench technique by introducing a compressible zone above the pipe. Made from discarded tires, tire-derived aggregate (TDA) has a high compressibility and is resistant to degradation. A new application, using TDA for induced trench rigid pipes is evaluated. A plane-strain finite element simulation is conducted, in which the constitutive curve of TDA measured from a large-scale compression test is implemented. Comparisons with other compressible materials show that TDA can provide similar benefits of load reduction for rigid pipes. A parametric study is carried out to optimise the design, including the geometry of the TDA zone, the spacing between the pipe and the TDA zone, and the relative stiffness between soil and TDA. Results show that earth pressures around the pipe decrease with the increase of the width of TDA zone but are not influenced significantly by its thickness. In the end, numerical data of the load coefficient for rigid pipes with TDA inclusions are compared with field measurements for other compressible inclusions and two analytical solutions. It is found that existing analytical approaches are applicable to the design of induced trench rigid pipes with TDA inclusions.